Research in personnel and human resources management. Vol. 39 - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E.; Halbesleben Jonathon R. B. (Emerald Publishing Limited, 2021)
Volume 39 of Research in Personnel and Human Resources Management contains eight original scholarly monographs written by thought leaders in the field of human resources management. This volume focuses on generational issues that have been created by a global pandemic, gig economy in relation to human resources management, immigrant and refugee issues in human resources management, pay dispersion issues, network structures and human resources management, human resources issues in family organizations and managing human resources during economic downturns.